Soočanje slovenske policije z gospodarsko kriminaliteto na sistemski ravni - Ferme, Jurij (Revija za kriminalistiko in kriminologijo, 2013)
Economic crime has been causing a great amount of damage to the Slovenian society, both materially and socially. Conditions to successfully control it include comprehensive, decisive and coordinated participation of all competentstate bodies and institutions, among which the police hold a special place. Economic crime-prevention must be strongly supported by politics and the society at large. In this article, documents, such as resolutions, strategies, action plans, police development plans and others, which regulate the facing of the police with challenges of economic crime at the systemic level since Slovenia's independence, are presented. The current Economic Crime Control Strategy in the Republic of Slovenia and the Police Action Plan for its implementation are addressed in detail. Focus is on the system of setting and achieving goals, programmes and tasks, as well as creating conditions for their execution. Special attention is directed at political support provided to the police. The latter is demonstrated primarily through the prism of providing funds for additional staff and equipment. Political support directed at controlling economic crime is compared to the support politics provided to the police when carrying out their tasks related to Slovenia's access ion to the European Union and Schengen. Comparisons concerning the number of criminal investigators in charge of investigating economic crime in 2002 and in 2013 are made, and statistics are shown for these types of criminal offences investigated by the police in the same periods, as well as statistics on "backlogs" that are stili awaiting investigation. The conclusion focuses on the possible reasons as to why actual political support provided to the police in the investigation of economic crime is not such as it is officially presented.
Keywords: action plan; akcijski načrt; criminal police; economic crime; gospodarska kriminaliteta; kriminalistična policija; nacionalni preiskovalni urad; načrt razvoja policije; National bureau of investigation; police; police development plan; policija; political support; politična podpora; strategija; strategy